2023
DOI: 10.1001/jamanetworkopen.2023.7473
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Reduce Severe Brain Injury Risk in Preterm Neonates

Abstract: ImportanceInterventions to reduce severe brain injury risk are the prime focus in neonatal clinical trials.ObjectiveTo evaluate multiple perinatal interventions across clinical settings for reducing the risk of severe intraventricular hemorrhage (sIVH) and cystic periventricular leukomalacia (cPVL) in preterm neonates.Data SourcesMEDLINE, Embase, CENTRAL (Cochrane Central Register of Controlled Trials), and CINAHL (Cumulative Index to Nursing and Allied Health Literature) databases were searched from inception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 227 publications
(614 reference statements)
0
4
1
Order By: Relevance
“…However, there are few studies to systemically investigate the associations between the practices and the occurrences of sIVH in detail. Different from the study [ 33 ], we did not find the practices of the antenatal corticosteroids and MgSO4 therapy were associated with the lower rate of sIVH. However, another systematic review indicated that although the antenatal MgSO4 could decreased the rate of IVH in preterm infant, this effect was not statistically significant.…”
Section: Discussioncontrasting
confidence: 99%
“…However, there are few studies to systemically investigate the associations between the practices and the occurrences of sIVH in detail. Different from the study [ 33 ], we did not find the practices of the antenatal corticosteroids and MgSO4 therapy were associated with the lower rate of sIVH. However, another systematic review indicated that although the antenatal MgSO4 could decreased the rate of IVH in preterm infant, this effect was not statistically significant.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, selection of suitable ventilator parameters tailored to the infant’s condition may help minimize the use of invasive ventilation. Volume-targeted ventilation and appropriate oxygen saturation target (85–89%) after birth could reduce the duration of mechanical ventilation, stabilize cerebral blood flow and reduce the incidence of BI ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prematurity affects approximately 1 in 10 births globally, whereas HIE affects 1.6 per 1000 live births in high-income countries and 12.1 per 1000 in low- or middle-income countries . Interventions to mitigate the risk of morbidities linked to prematurity and HIE are limited, leaving affected infants at an elevated risk of neurodevelopmental complications that adversely affect motor skills and cognitive abilities. While various neurodevelopmental concerns exist, cognitive impairment and cerebral palsy stand out as primary concerns, affecting approximately 16.9% and 6.9% of very preterm infants, respectively .…”
Section: Introductionmentioning
confidence: 99%